(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the physiotherapy techniques in the thoracic surgery clinic in Turkey. Materials and Methods: The data of this research was obtained through the online questionnaire created by the authors. The questions in the questionnaire were created by the researcher in parallel with the literature (14 questions). In the questionnaire, descriptive information was asked using multiple-choice question types about chest surgery clinics and applied physiotherapy. A chest surgeon from each participating clinic was asked to respond to the questionnaire. Results: A total of 62 clinics participated in the study. The mean number of monthly operations of these clinics is 0-20 in 51.6%, 21-40 in 19.4%, and 41-60 in 19.4%. 64.5% of the clinics participating in the study perform regular physiotherapy practices to their patients. The clinics that applied pulmonary rehabilitation to their patients, 65% of them additionally performed pulmonary rehabilitation in the preoperative period. The most common applications were early mobilization, airway cleaning techniques, deep breathing exercises, assisted coughing, humidification of the airway, incentive spirometer exercises, forced expiration, and exercise practices. 53.3% of the clinics where routine physiotherapy was administered benefited from assistive devices for pulmonary rehabilitation. Conclusion: Although physiotherapy practices are performed in the thoracic surgery clinic in Turkey, they are not at the desired level. Preoperatively pulmonary rehabilitation practice in thoracic surgery is even rarer. Moreover, the content of pulmonary rehabilitation programs is not standard. The prevalence of evidence-based physiotherapy applications should be increased in thoracic surgery clinics.